PREVALENCE OF ASSOCIATIONS BETWEEN GRAVES - BASEDOW DISEASE AND DIABETES OR OTHER GLYCEMIC CHANGES IN AN ADULTS GROUP - Adriana, Gherbon (European Scientific Journal, ESJ, 2014)
Background&Aims: Thyroid disorders are frequently associated with diabetes in clinical practice. The purpose of this study is to assess prevalence of associations between Graves - Basedow disease and diabetes or other changes in glycemic balance in an adults group. Methods: The studied group was of 650 people with diabetes and other changes in glycemic balance aged between 18 and 79 years. The methods of investigation were represented by clinical, imaging, biochemical, hormonal and immunological parameters. Results: The prevalence of Graves – Basedow disease in the study group was 22.61% (21.76% F vs. 30.64% M, p = 0.11, X2 = 2.53). Graves – Basedow disease prevalence for type 1diabetes was 10% (9.09% F and 20% M, p = 0.38, X2 = 0.75), 20.68% for type 2 diabetes (21.03% F and 18.42% M, p = 0.71, X2 = 0.14), 23.49% for impaired glucose tolerance (IGT) (23.12% F and 30% M, p = 0.61, X2 = 0.25), and 32.47% for impaired fasting glucose tolerance (IFG) (27.77% F and 88.88% M p = 0.00016, X2 = 14.15). Significant differences in this prevalence were found only between type 1 diabetes and other changes in glycemic balance (10% vs. 23.49%, p = 0.023, X2 = 5.11 for IGT, 10% vs. 32.47%, p = 0.001, X2 = 10.73 for IFG). Conclusions: Graves – Basedow disease was mainly associated with IGT and IFG that occurred due to the presence of excess thyroid hormone. We don’t find significant differences in the gender (except IFG - predominantly in males).